2011
DOI: 10.1002/hed.21452
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, MDM2, p21, heat shock protein 70, and HPV 16/18 E6 proteins in oral verrucous carcinoma and oral verrucous hyperplasia

Abstract: Immunohistochemistry with the above-cited 5 biomarkers could not help differentiate oral verrucous hyperplasia from oral verrucous carcinoma. The low expression of p21 may partially explain abnormal epithelial overgrowth in both verrucous lesions. The pathogenesis of both verrucous lesions may be at least partially attributed to the overexpression of MDM2 protein and moderate expression of HSP 70 protein in both lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
1
30
1
1
Order By: Relevance
“…However, other studies have concluded that p53 is a poor marker for discriminating between both entities. 31 Although the diagnostic value of e-cadherin has been statistically demonstrated by some, 28 this has not been confirmed by others. 30 Our immunohistochemical results are consistent with the ones usually found for pseudocarcinomatous hyperplasia, rather than for SCC or verrucous carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…However, other studies have concluded that p53 is a poor marker for discriminating between both entities. 31 Although the diagnostic value of e-cadherin has been statistically demonstrated by some, 28 this has not been confirmed by others. 30 Our immunohistochemical results are consistent with the ones usually found for pseudocarcinomatous hyperplasia, rather than for SCC or verrucous carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…No obstante, lo que supondría un cambio radical en el pronó stico de esta entidad sería la obtenció n de marcadores de la saliva del paciente, investigació n que se está desarrollando de forma cada vez má s creciente 57 . Así, estudios recientes como el de Jancsik et al 58 aseguran que en aná lisis de saliva se han encontrado sobreexpresiones proteicas de anexina A8 y peroxideroxina-2, que han sido descritas previamente en muestras de cá ncer oral, por lo que es posible que la saliva pueda ser usada como mé todo de detecció n de cá ncer oral en etapas tempranas; si bien los resultados son esperanzadores, está n lejos de la efectividad necesaria 59 .…”
Section: Tablaunclassified
“…30 This system allows the typing of both high-risk HPV (types 16,18,26,30,31,33,35,39,45, 51, 52, 56, 58, 59, 66, 68, 70,73, 82i and 82m) and low-risk HPV (6,11,34,40,42,43,44,54,55,57,61,64,71,72,81 and CP6108).…”
Section: Hpv Dna Detection and Typingmentioning
confidence: 99%
“…2,39 In addition, as known from the literature, the exact distinction between verrucous hyperplasia and verrucous carcinoma is not clearcut and the exact criteria are lacking. 3,40 Previous studies concluded that verrucous carcinoma from mucosal areas are related to mucosal HPV types and verrucous carcinoma located in cutaneous areas are not specifically linked to any specific group of HPV. 41 In this study, we found that mucosal types were indeed restricted to mucosal lesions, that is, high-risk HPV in a verrucous carcinoma of the head and neck region and low-risk HPV types in giant condylomas of the anus and vulva, whereas cutaneous HPV types were detected in a verrucous hyperplastic lesion of the penis.…”
Section: Human Papillomavirus In Verrucous Carcinomamentioning
confidence: 99%